Penerapan Model Inkuiri untuk Meningkatkan Hasil Belajar Matematika Kelas IV SD Negeri 36/VI Rantau Panjang - Kurnia Ilahi; Randi Eka Putra; Megawati Megawati (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The limited active engagement and subpar academic performance in Mathematics among fourth-grade students at SD Negeri 36/VI Rantau Panjang served as the underlying rationale for initiating this study. The persistence of conventional instructional methods has been identified as a contributing factor to students diminished learning drive, minimal involvement, and lack of enthusiasm toward classroom activities. This research aimed to articulate the implementation of the inquiry-based learning model in enhancing both the instructional process and academic outcomes in Mathematics. The study adopted a Classroom Action Research (CAR) framework, executed in two iterative cycles encompassing the phases of planning, execution, observation, and reflection. Data collection instruments included structured observation sheets to monitor teacher and student behavior, as well as assessments designed to gauge learning outcomes. The findings demonstrated that applying the inquiry-based approach exerted a constructive influence on boosting students’ active participation during instruction and contributed significantly to improving their academic achievement. By the end of each cycle, there was a notable increase in the number of students attaining the Minimum Mastery Criteria. Based on these results, it is inferred that the inquiry model is effective in elevating the quality of teaching and learning in Mathematics. Moreover, this approach holds considerable promise for broader application as an active learning strategy suitable for the elementary level